A comparative analysis and an optimized structure of vertical GaN floating gate trench MOSFET for high-frequency FOM. (1st July 2022) - Jaiswal, Nilesh Kumar; Ramakrishnan, V N
Abstract: A vertical GaN floating gate trench MOSFET (FG-MOSFET) device structure has been optimized to obtain an enhanced high-frequency figure of merit (HF-FOM) than the conventional SGT- and TG-MOSFET. The floating gate (FG) electrode helps to reduce the surface electric field and binges in the middle of the drift layer. Using TCAD simulation, we demonstrate that with proper design of trench depth, drift doping, and field plate oxide thickness, the corresponding electric-field distribution for FG-MOSFET can be reduced to 2.3 MV cm −1 . The proposed device has been designed for 600 V blocking voltage capability and with a specific on-resistance ( R on ) as low as 0.73 mΩ cm 2 due to the higher drift doping concentration. The HF-FOM ( Q GD × R on ) of FG-MOSFET shows a lower by two times and four times compared to SGT- and TG-MOSFET, due to FP oxide. Our results show that the FG-MOSFET device produces 15% and 47% reductions in the switching energy losses when compared with the similar current rated SGT- and TG-MOSFET devices, respectively.